Macro-Modeling Linguistic Variability: Expanding the Boundaries of Linguistic Variation Studies (A Comprehensive Review of Russian Linguists’ Works) - N. D. Golev (Научный диалог, 2023)
This paper presents a comprehensive review of contemporary works by Russian linguists on the topic of linguistic variation. The aim of the review is to identify universal foundations for systematizing the diverse manifestations of this concept in language and speech, as reflected in linguistics. The main focus of the review is on two parameters of macromodeling linguistic variability: structural-level and functional-discursive. The first is associated with “enlarging” the subject of variation studies from phonemes to texts, while the second parameter is related to considering various phenomena of speech activity in terms of variation, such as language consciousness, language personality, and formats of speech activity (goals, discourses, speech genres, etc.). The relevance of this research is determined by the context of the emergence of variation studies as a universal direction in language research. A monitoring of linguistic works on variation shows that linguistics in this aspect is developing along the lines of globalization. The material for this study was collected from publications on Elibrary.ru from 2000 to 2023. The focus was primarily on works that explicitly mentioned concepts related to the ontological manifestations of linguistic variation and the epistemological trend towards their metalinguistic globalization.